2017
DOI: 10.1016/j.toxrep.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potential health risks associated with the aluminium, arsenic, cadmium and lead content in selected fruits and vegetables grown in Jamaica

Abstract: HighlightsThirteen food crops were analysed for aluminium, arsenic, cadmium and lead.Mean concentrations were used to calculate EDI, THQ and HI.TCR was calculated for arsenic for all food crops.The THQ and HI were <1 for all food crops; target cancer risk did not exceed 10−4.The food crops evaluated pose no undue risk to the consumer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
111
12
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(152 citation statements)
references
References 19 publications
7
111
12
7
Order By: Relevance
“…Bivalves may reach relatively very high Pb contents even in comparison with other seafood groups, just as seen in current study (Table ), and fail to comply with upper Pb limits (Miedico et al , ). Low Pb contents in vegetables, similar to those of the current study, have been reported by other authors (Antoine et al , ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Bivalves may reach relatively very high Pb contents even in comparison with other seafood groups, just as seen in current study (Table ), and fail to comply with upper Pb limits (Miedico et al , ). Low Pb contents in vegetables, similar to those of the current study, have been reported by other authors (Antoine et al , ).…”
Section: Resultssupporting
confidence: 93%
“…Though it has been reported that cruciferous vegetables can accumulate high amounts of Cd and Pb (Kabata‐Pendias, ), the current study's results seem to indicate that being a crucifer may not be the most determining aspect in this case. It should also be mentioned that pollution and other environmental factors may lead to relatively higher Cd contents in vegetables (Antoine et al , ; Dziubanek et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Where EDI is the estimated daily metal intake of the population in mg/day/kg body weight and RfD is the oral reference dose (mg/kg/day) values for each metals of interest and as listed in Table 1. If the value of THQ is < 1, it is generally presumed to be safe for the risk of noncarcinogenic effects and if it is > 1, it is supposed that there is a chance of noncarcinogenic effects with an increasing probability as the value upsurges [45,52].…”
Section: Thq ¼ Edi Rfd ð3þmentioning
confidence: 99%
“…Hazard Index (HI). It has been documented that the individual health risks of the analysed heavy metals in the same vegetable are accumulative and that is expressed as hazard index (HI) [43,45,[50][51][52][53][54][55][56]. Accordingly, the HI of target metals considered in this study are calculated using Eq (4) [52,53].…”
Section: Thq ¼ Edi Rfd ð3þmentioning
confidence: 99%
See 1 more Smart Citation